1992
DOI: 10.1126/science.256.5055.385
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of Water Channels in Xenopus Oocytes Expressing Red Cell CHIP28 Protein

Abstract: Water rapidly crosses the plasma membrane of red blood cells (RBCs) and renal tubules through specialized channels. Although selective for water, the molecular structure of these channels is unknown. The CHIP28 protein is an abundant integral membrane protein in mammalian RBCs and renal proximal tubules and belongs to a family of membrane proteins with unknown functions. Oocytes from Xenopus laevis microinjected with in vitro-transcribed CHIP28 RNA exhibited increased osmotic water permeability; this was rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
1,259
3
21

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,901 publications
(1,317 citation statements)
references
References 29 publications
34
1,259
3
21
Order By: Relevance
“…Aquaporins play a significant role in recovery from water deficit in both prokaryotic and eukaryotic cells [1,38]. Expression of aquaporin genes are regulated under water stress treatments in many plant species [17,18,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquaporins play a significant role in recovery from water deficit in both prokaryotic and eukaryotic cells [1,38]. Expression of aquaporin genes are regulated under water stress treatments in many plant species [17,18,[20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Transmembrane water transport occurs by diffusion through the lipid bilayer and/or by increased membrane permeability due to the water channel proteins, aquaporins [1]. The presence of aquaporins, a class of major intrinsic proteins (MIPs), enables fast and controlled translocation of water across the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The estimated number of functional C!-IIP28 molecules per vesicle is (~13, considering that the siagle water channel Pf is 6.8-16 x 10 -~4 cm3/s [6,9], the vesicle slrface area is 3.14x 10 -~° cm 2 and that APf (defined as C HIP28-containing vesicle Pf-control vesicle Pf) is 2.8 x 10 .3 c~ ~/s. Several water channel characteristics were verified, in p,.rticular a low activation energy value and sensitivity to a cl tssical mercurial sulfhydryl reagent.…”
Section: Discussionmentioning
confidence: 99%
“…The functional characterization of CHIP28 has so far been essentially performed by micro-injecting in vitro-transcribed cRNA into Xenopus laevis oocytes [6] and by reconstituting purified CHIP28 into proteoliposomes [7][8][9]. In the present work, we investigated a new heterologous expression system for CHIP28 production and functional analysis: a Saccharomyces cerevisiae temperature-sensitive mutant strain, defective in the final step of the secretory pathway (sec mutant) [10], which has already been successfully used for the expression of membrane proteins [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Based on results from the present study, this carrier may be closely related to water uptake. The earlier view is that water molecules enter into cells through passive diffusion, but recently, it has been suggested that some specialized water transport carriers like aquaglyceroporins play an important role (Luu and Maurel 2005;Preston et al 1992). The aquaglyceroporins, a class of water channel not only permeable to water molecules but also permeable to glycerol and small solutes (Thomas et al 2002), have been identified as carriers of As in bacteria, yeast, humans, and other vertebrates (Mukhopadhyay et al 2014) but not found in the As hyperaccumulator yet (Mathews et al 2011).…”
Section: Discussionmentioning
confidence: 99%